2021
DOI: 10.1097/phm.0000000000001719
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Ultrasound as a Motivator for Selecting a Physical Medicine and Rehabilitation Residency Program in the United States

Abstract: This study aimed to determine the influence of musculoskeletal ultrasound (MSKUS) curriculum on applicants during the residency-selection process. A survey of 666 applicants for the Johns Hopkins University, Mayo Clinic, and Harvard/Spaulding Rehabilitation Physical Medicine and Rehabilitation programs was conducted in June 2020. A total of 180 respondents scored the influence of a MSKUS curriculum on their decision making for residency selection. In addition, applicants were asked to rank specific areas of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Musculoskeletal ultrasound and injection skills remain important considerations for PM&R residents. [14][15][16][17][18] Up to 71% of prospective PM&R residency applicants rate the presence of a musculoskeletal ultrasound curriculum as "very important" or "absolutely essential" in deciding whether to interview at a residency program. 13 A survey of PM&R residency program directors highlighted several barriers to teaching musculoskeletal ultrasonography including insufficient expertise of instructors, poor access to equipment, and lack of structured curricula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal ultrasound and injection skills remain important considerations for PM&R residents. [14][15][16][17][18] Up to 71% of prospective PM&R residency applicants rate the presence of a musculoskeletal ultrasound curriculum as "very important" or "absolutely essential" in deciding whether to interview at a residency program. 13 A survey of PM&R residency program directors highlighted several barriers to teaching musculoskeletal ultrasonography including insufficient expertise of instructors, poor access to equipment, and lack of structured curricula.…”
Section: Discussionmentioning
confidence: 99%
“…However, at least 20% of residents do not meet the minimum requirements for Ultrasound. Musculoskeletal ultrasound and injection skills remain important considerations for PM&R residents 14–18 . Up to 71% of prospective PM&R residency applicants rate the presence of a musculoskeletal ultrasound curriculum as “very important” or “absolutely essential” in deciding whether to interview at a residency program 13 .…”
Section: Discussionmentioning
confidence: 99%
“…As more and more residency programs involved in rehabilitation are incorporating ultrasound in their curriculum ( 1 , 2 ) and as many practicing rehabilitation professionals are getting trained in both basic and advanced ultrasonography ( 3 , 4 ), the applications of this technology within our field increase.…”
mentioning
confidence: 99%
“…2,3 An increasing number of PM&R residents are pursuing careers that use US, 4,5 and in a recent survey of medical students interested in physiatry, 92% indicated that they were "likely" or "very likely" to use US in their future practice. 6 In 2015, the Accreditation Council for Graduate Medical Education Review Committee for PM&R established an acceptable minimum exposure of at least 10 observed or performed US procedures during residency training. 7 However, these limited procedure numbers are unlikely to adequately prepare physicians to perform these injections effectively in independent practice.…”
mentioning
confidence: 99%